P10 Correlation of aortic valve calcification on CT with aortic valve area estimated by the continuity equation using transthoracic echocardiography. (7th September 2020) - Foley, R; Lyen, S; Manghat, N; Hamilton, M
Abstract : Introduction: The latest guidelines from the European Society of Cardiology on the management of valvular heart disease have recommended the use of calcium scoring of the aortic valve (AoV) on computed tomography (CT) in patients with severe aortic stenosis (AS) on echocardiography (Baumgartner, Falk, et al., 2017). The objective of this study was to calculate the AoV calcification in patients with severe AS on echocardiography. Methods: Data was prospectively collected on all patients undergoing CT for consideration of transcatheter aortic valve implantation (TAVI) from July 2019 - January 2020. CT was performed on multidetector scanners, (Siemens SOMATOM AS+ and Canon Aquilion ONE) and measurements of AoV calcification and AoV area were performed using validated software (TeraRecon, California). Severe AS was defined as an aortic valve area of <1 cm 2 on echocardiography. Pearson correlation analysis was performed using R v3.3.3. Results: The cohort consisted of 81 patients, 18 of whom contemporaneous echocardiography was available. There were a range of AoV calcium scores from 373–5478, with a mean score of 2, 832 arbitrary units. There was a very weak negative correlation between the AoV area and the AoV calcification r=-.06, p=0.42 (Pearson's). This relationship was not statistically significant. Conclusion: In patients with severe aortic stenosis on echocardiography, there is no correlation between AoV calcification and AoV area. It is important to understand the relationship between AoV calcification and AoV area before its use in clinical practice can be advocated.